Peran Agama dalam Pembentukan Dasar Falsafah Negara dan Membangun Keutuhan Negara Kesatuan Republik Indonesia (NKRI) - Nurah Nufaisah; Nabila Eka Ramadhani Wahyudi; Erwin Kusumastuti (Atta'dib Jurnal Pendidikan Agama Islam, 2021)
Indonesia is a country of many different religions and beliefs. In Indonesia there are six religions recognized by the state. Of the many religions of Indonesia, religion plays an indirect role in creating a mind-set in each of its people. Based on these differences, it led to the creation of an ideology of the state not through easy process but through long discussions of predecessors who held high regard for the godhead. Judging from the many religious teachings that exist, it has presented its own challenge as to the extent of the role religion plays in ideologies that are capable of resolving conflict of differences within the country. Therefore, to address the issue, this writing deals with the relationship and implications of religious values at the base of the Indonesian state of pancasila, using the hermeneutical method that focused on philosophical excavation of the early idea of the establishment of the state of Indonesia. The study results in that within each of them please pancasila there are always religious values and application forms in every aspect of domestic life. It may be concluded that religion and countries have a relationship that is believed to bring legal and social pluralism into the unity of the republic of Indonesia.